First molecular evidence for bat Betacoronavirus in Mindanao - Tampon, Nikki Vanesa T.; Onggo, Lowela Siarot; Murao, Lyre Anni E.; Achondo, Marion John Michael M.; Valila, Agape Shelley D.; Burgos, Sammer C.; Bacus, Michael G.; Libre, Jr., Kemuel; Malbog, Kameela Monique A.; Rabaya, Ysabela Marie C. (2020)
Coronaviruses (CoVs) are common agents of respiratory and gastrointestinal tract infections but are also considered as important emerging infectious disease (EID) agents that have led to global epidemics of severe respiratory disease. Human CoV EIDs have been proposed to have originated from bat CoVs (BtCoV). This study reports the detection of CoV in bats from the University of the Philippines (UP) Mindanao, Davao City using an optimized reverse transcription nested polymerase chain reaction (RT-nPCR) for bat CoV RNA-dependent RNA polymerase (RdRp) gene. Out of 49 bats, only one was positive for the virus (2.04% detection rate). Phylogenetic analysis demonstrated the genetic relatedness of the CoV, which was detected in the fruit bat Macroglossus minimus, to other bat and mammalian CoVs of betacoronavirus under sub-group 2d. The CoV also exhibited 94.55% identity and close genetic relationship with BtCoV 2265/Philippines/2010 from Luzon, Philippines, suggesting a common lineage of these viruses that may have pre-existed prior to biogeographic movements of bats in the country. This is the first reported detection of CoV in bats from Mindanao, hence further surveillance of circulating viruses in wildlife is recommended to expand the understanding of BtCoV evolution and potential for zoonosis. These findings also emphasize the need to limit potential zoonotic transmissions through bat-animal or human interactions by preserving natural habitats. (Author's abstract)
Includes bibliographical references (pages 93-94)
Keywords: Biology; Bat coronaviruses; Betacoronavirus; Macroglossus minimus